2017
DOI: 10.1111/jvim.14721
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofMollicutesMicroorganisms in Respiratory Disease of Cattle and Their Relationship to Clinical Signs

Abstract: BackgroundBovine respiratory disease (BRD) is an important problem in cattle production that is responsible for economic losses in dairy herds. Mycoplasma spp. are described as an important etiological agent of BRD.HypothesisTo evaluate the occurrence of the most important mycoplasmas in the lower respiratory tract of healthy and BRD cattle in relationship to clinical signs of BRD.AnimalsSixty young dairy cattle were classified as healthy (n = 32) or cattle showing clinical signs of BRD (n = 28).MethodsTrachea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
0
21
1
2
Order By: Relevance
“…The use of more than one culture medium may increase the isolation rate of Mycoplasma spp., as observed by Lai et al (1986), when comparing Chalquest and Hayflick's means for detecting M. pulmonis, with 92% and 66% bacterial isolation, respectively. Tortorelli et al (2017) obtained only positive isolation on Hayflick medium in 32 sections of bovine respiratory disease, stressing a low percentage when compared to other studies. The authors also observed that the result of bacterial isolation is often not associated with PCR in a positive way, comprising negative molecular and positive culture results.…”
Section: Microbiological Analysiscontrasting
confidence: 54%
“…The use of more than one culture medium may increase the isolation rate of Mycoplasma spp., as observed by Lai et al (1986), when comparing Chalquest and Hayflick's means for detecting M. pulmonis, with 92% and 66% bacterial isolation, respectively. Tortorelli et al (2017) obtained only positive isolation on Hayflick medium in 32 sections of bovine respiratory disease, stressing a low percentage when compared to other studies. The authors also observed that the result of bacterial isolation is often not associated with PCR in a positive way, comprising negative molecular and positive culture results.…”
Section: Microbiological Analysiscontrasting
confidence: 54%
“…It is not clear what role M. dispar plays in respiratory health. This bacterium has been previously isolated from the lungs of both healthy and pneumonic cattle [48][49][50]. Interestingly, a study by Timsit et al, 2018 identified a distinct metacommunity, which was characterized by an over-representation of M. dispar (and other commensal bacteria such as Lactococcus lactis and Lactobacillus casei) in the lungs of healthy feedlot cattle.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear what role M. dispar plays in respiratory health. This bacterium has been previously isolated from the lungs of both healthy and pneumonic cattle [48][49][50]. immunosuppressive effects, it is associated with only milder respiratory infections and is likely not a causative agent for BP [48,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium has been previously isolated from the lungs of both healthy and pneumonic cattle [48][49][50]. immunosuppressive effects, it is associated with only milder respiratory infections and is likely not a causative agent for BP [48,50,51]. In general, Mycoplasma have a high affinity for binding to respiratory epithelial cells via adhesin proteins [52,53].…”
Section: Discussionmentioning
confidence: 99%